Hereditary "pure" spastic paraplegia: a study of nine families. - Polo, J M (1993)
The genetic and clinical features of 46 patients in nine families with "pure" hereditary spastic paraplegia are described. Inheritance was autosomal dominant in seven families and autosomal recessive in two. In dominant kinships, five families corresponded to type I with onset below 35 years, and two to type II with onset over 35 years. In early onset dominant families, in spite of apparent complete penetrance before 20, variable expression and incomplete penetrance occurred. Irrespective of genetic type, serial evaluation revealed that the main symptom consisted of slowly progressive spastic gait, extremely variable in severity, associated in some patients with decreased vibratory sense and micturition disorders generally as late features. In dominant families, the disease tended to be more severe in late onset cases. No patient had symptoms in the upper limbs and plantar responses were flexor in six symptomatic patients. Central motor conduction time studied by transcranial magnetic stimulation was always normal in the upper limbs and increased in the lower limbs in five of the eight patients on whom it was performed. Monomorphic and stereotyped clinical pattern in this series does not support the concept of multisystem involvement of the central nervous system as a hallmark of the disease.